PENGARUH MODEL E-LEARNING DAN GAYA BELAJAR TERHADAP PRESTASI BELAJAR SISWA (Studi Eksperimen Pada Mata Pelajaran Fisika Kelas X MIPA SMAN 1 Pagar Gunung) - Yulinawati Yulinawati (UNIB Press, 2020)
The purpose of this study was to determine the effect of e-learning models and learning styles on the learning achievement of students studying physics in class X SMA Negeri 1 Pagar Gunung with a population of 90 students. The study design used a 2 x 2 factorial design. The sample selection technique was purposive random sampling. Data for achievement tests are multiple choice questions and questionnaires for learning styles. Data processing using two-way analysis of variance analysis with a significance level of 0.05. The results of the study are: (1) student learning achievement e-learning model obtained an average value of 15.57 while the discovery learning model 13.07 (2) student learning achievement visual style an average of 16.46 while the auditory learning style 12.18 (3) There is an interaction between learning models and learning styles on student achievement. (4) student achievement with visual learning style e-learning model is higher than discovery learning model (5) student learning achievement with auditory learning style e-learning model is higher than discovery learning model.